Therapists’ Perception of their Relationship with Educational Staff In Secondary Inclusive Schools - Fogel -Simhony, Meytal (Advances in Social Sciences Research Journal, 2021)
Due to the disparities inherent in the role perception of expressive and creative therapists in the Israeli educational system, and the difficulty of fulfilling the role in an optimal manner for all parties involved, this study aims to examine the role perception of the therapist in secondary schools with inclusive education, examining the therapist’s work vis-a-vis the school’s educational staff and its management team.The sample included 11 therapists who have worked in a secondary school for over two years. The data was collected through semi-structured interviews. Findings of the study indicated a number of significant parameters in the therapist's work vis-à-vis the staff. Moreover, it is evident that the therapist's own role perception is related to the role perception as perceived by the educational and management team. The discussion examines the significance of the disparity between the therapist's role perception and the expectations and perceptions of the staff within the educational system.